1984
DOI: 10.1002/bsl.2370020109
|View full text |Cite
|
Sign up to set email alerts
|

Towards an empirical model of malingering and deception

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 116 publications
(53 reference statements)
1
33
0
5
Order By: Relevance
“…Although there are theoretical principles and various methods to assess malingering, there is a two-fold ''built-in'' difficulty in this area. Rogers [1984b] observed that (1) there are no psychological measures which are not fakeable, and (2) frequently there is no way to verify cases of malingering.…”
Section: Inconsistencies Within and Between Tests Performancementioning
confidence: 95%
“…Although there are theoretical principles and various methods to assess malingering, there is a two-fold ''built-in'' difficulty in this area. Rogers [1984b] observed that (1) there are no psychological measures which are not fakeable, and (2) frequently there is no way to verify cases of malingering.…”
Section: Inconsistencies Within and Between Tests Performancementioning
confidence: 95%
“…Especially in states which have a death penalty, the motivation to feign amnesia would be considerable. Indeed, Rogers and Cavanaugh (1983), in an article on malingering, suggested that such behavior might be best conceptualized in terms of "coping strategies, good judgment, and survival" (p. 446). Given the potential for deception (Resnick, 1984), it is of obvious importance that an examining clinician be able to distinguish between genuine and feined amnesia.…”
Section: Clinical Issuesmentioning
confidence: 98%
“…For example, Parwatiker, Holcomb, and Menninger ( 1985) discovered that certain historical information reliably distinguished between confessed murderers and those who were convicted but claimed amnesia. Among the most reliable distinguishing variables were drug and alcohol intoxication and elevations on MMPI scales Hs, Hy, and D (see Rogers, 1984 for a review of studies examining the usefulness of the MMPI in detecting malingering). Such results are consistent with an interpretation that these individuals had a genuine hysterical or dissociatively based amnesia.…”
Section: Clinical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…De ahí que se hayan desarrollado pruebas para evaluar la simulación unicamente en adultos, (Rogers, 1984b;Rogers, 1997;Rogers, Gillis & Bagby, 1990;Rogers, Gillis, Dickens et al, 1991;Rogers, Jackson, Sewell et al, 2005;Rogers, Kropp, Bagby et al, 1992;Schretlen, 1986;Smith, Borum & Schinka, 1993;Smith & Burger, 1997).…”
Section: Introductionunclassified